The survivin gene expression in neoplastic hepatocytes from chickens infected with Marek’s virus - NASIRI, R.; GHOLAMI-AHANGARAN, M.; EBADI, P. (Journal of the Hellenic Veterinary Medical Society, 2019)
P53 protein is one of the main proteins in apoptosis pathway. The role of survivin protein in inhibition of P53 in different human cancers has been proved. The expression of survivin can be a main marker in diagnosis and prognosis of different human cancer. Until now, the survivin gene expression in birds infected with Marek’s disease was not investigated. In this study, liver tissue samples of chickens infected with Marek’s disease virus (MDV) was collected. The identification of MDV was carried out with PCR and histopathologic examination. After identification of MDV, the pathogenicity of infected virus was investigated with specific primers targeted on 132 bp tandem repeat. After this, the survivin gene expression was examined in neoplastic liver samples by Real-Time PCR. The PCR amplification of tumor liver samples showed that all samples were infected with MDV. The result of histopathology and amplification of 132 bp tandem repeat in tumor samples showed that the chickens were infected to pathogenic MDV. Results showed that the survivin gene expression in neoplastic hepatocytes was significantly higher than normal hepatocytes. In conclusion, survivin gene expression can be utilized as a suitable biomarker in diagnosis of Marek’s disease in birds. It seems that viral meq oncogene in Marek’s disease can play role in induction of survivin expression in this disease that it is necessary to be proved.